2018
DOI: 10.1371/journal.pone.0203473
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal medicine reduced the risk of stroke in patients with Parkinson’s disease: A population-based retrospective cohort study from Taiwan

Abstract: Parkinson’s disease (PD) is associated with a significantly increased risk of stroke. Traditional Chinese medicine (TCM) has long been used in Asia to treat stroke, but there are no large-scale clinical data to confirm its efficacy in protecting PD patients against stroke. Herein, we analyzed a cohort of 1,000,000 records from Taiwan’s National Health Insurance Research Database for the period 1997–2011, and identified 1,882 patients with new-onset PD. We matched 290 patients who received Chinese herbal medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…36 Our data suggest that OA-acupuncture cohort was significantly less costly to care for and our finding is similar to other Taiwanese reports that showed that TCM services are associated with lowest medical expenditure. 37,38 Limited physical activity, which is mainly caused by OA of the hip or knee, is considered a known risk factor for CHD. 39 At the same time, there is evidence to support the use of exercise to improve the damage of the joints and alleviate pain.…”
Section: Discussionmentioning
confidence: 99%
“…36 Our data suggest that OA-acupuncture cohort was significantly less costly to care for and our finding is similar to other Taiwanese reports that showed that TCM services are associated with lowest medical expenditure. 37,38 Limited physical activity, which is mainly caused by OA of the hip or knee, is considered a known risk factor for CHD. 39 At the same time, there is evidence to support the use of exercise to improve the damage of the joints and alleviate pain.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also considered comorbidities that cause a stroke. According to previous studies ( Lai et al, 2018 ; Jang et al, 2019 ), we selected the following comorbidities related to stroke: hyperlipidemia (ICD-9-CM code 272); diabetes mellitus (ICD-9-CM code 250); hypertensive disease (ICD-9-CM codes 401–405); coronary heart disease (ICD-9-CM codes 410–414); acute pulmonary heart disease (ICD-9-CM code 415); cardiac dysrhythmia (ICD-9-CM code 427); congestive heart failure (ICD-9-CM code 428); atherosclerosis (ICD-9-CM code 440); peripheral vascular disease (ICD-9-CM code 443.9); and other venous embolism and thrombosis (ICD-9-CM code 453). Patients with stroke were identified using ICD-9-CM codes 430 to 438.…”
Section: Methodsmentioning
confidence: 99%
“…However, AGING none of the therapeutic agents in previously could slow down the loss of neuronal cells so as to decelerate or halt the progression of PD [4,5]. Levodopa-resistant symptoms even conduce to disability and significantly increase the risk of all-cause mortality [6]. Thereby, it is crucial and urgent to search appropriate therapeutic agents with better treatments for PD with western medicine.…”
Section: Introductionmentioning
confidence: 99%